ORIENTASI PENDAMPINGAN PERLINDUNGAN HARTA ANAK YATIM OLEH WALI DALAM QS AN NISA AYAT 2 DI MAJLIS TA’LIM AN-NUR BABELAN, BEKASI - Kholilurrohman Kholilurrohman; Nurkhafifah Tamsyur; Mohamad Zainal Arifin; Salman Faris; Ahmad Husnul Hakim; Wardatul Jannah (MPP: Lembaga Penelitian Dan Studi Kebijakan, 2025)
Islamic law instructs the guardians of orphans not to arbitrarily affect the orphans and their property. Because children are part of the younger generation as one of the human resources who have a strategic role in forming a better family. Guardians should not behave unjustly towards orphans. he law recommends the guardian to make a list of assets so that the guardian's property is not mixed with the orphan's property and in Law No. 1 of 1974 concerning Marriage, it is regulated about the prohibition of using and consuming excessively, moving and selling the 1 Nurkhafifah Tamsyur property of orphans. However, the reality of society, in the care of orphans has not been carried out as specified in Islamic teachings. In maintaining the property of an orphan by a guardian, the guardian must have a concept in managing finances on a monthly or yearly basis, it is better if he develops his property so that it is